Non-paralytic motor disturbances and speech disorders: the role of the supplementary motor area. - Gelmers, H J (1983)
A right-handed patient with a lesion demonstrated by CT to involve the right medial frontal cortex is described. He exhibited a strong contralateral grasp reflex, motor perseveration and the presence of purposeful movements that appeared to be dissociated from conscious volition. In addition, there was a disorder of speech consisting of a lack of spontaneous speech production, with preserved ability to imitate. It is suggested that these disorders are due to damage to the supplementary motor area.